2003
DOI: 10.1002/ijc.11285
|View full text |Cite
|
Sign up to set email alerts
|

IL‐18 is produced by prostate cancer cells and secreted in response to interferons

Abstract: Key words: IL-18; caspase-1; prostate cancer; prognosis; IFN-␥; IFN-␣IL-18 was first identified as an IGIF based on its ability to induce high levels of IFN-␥ secretion by both NK cells and Th1 clones. 1,2 IL-18 belongs to the IL-1 family, 3 lacks a signal sequence 2 and is processed into an 18 kDa mature form by caspase-1. 4 It is mainly produced by macrophages and dendritic cells. However, we and others have shown that IL-18 is also synthesized by nonimmune cells. 5 IL-18 potentiates IL-12-induced Th1 develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…23 This effect, together with a role of IL-18 in effective priming of CTL and Th1 cells, appears to be an important factor for the effective elimination of tumor cells. 8 The wide range of IL-18 expression in epithelial neoplasia, including human colon carcinoma, 34 malignant skin tumors, 43 ovarian carcinoma, 44 squamous cell carcinoma cells, 45 prostate cancer cells 46 and, head and neck cancer 47 raises the issue whether drug-induced IL-18 processing is relevant to these tumor entities as well. As in pancreatic carcinoma (this study), the cytokine is predominantly produced intracellularly and secreted by these epithelial tumor cells as the unprocessed 24-kDa inactive precursor requiring proteolytic processing for activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 This effect, together with a role of IL-18 in effective priming of CTL and Th1 cells, appears to be an important factor for the effective elimination of tumor cells. 8 The wide range of IL-18 expression in epithelial neoplasia, including human colon carcinoma, 34 malignant skin tumors, 43 ovarian carcinoma, 44 squamous cell carcinoma cells, 45 prostate cancer cells 46 and, head and neck cancer 47 raises the issue whether drug-induced IL-18 processing is relevant to these tumor entities as well. As in pancreatic carcinoma (this study), the cytokine is predominantly produced intracellularly and secreted by these epithelial tumor cells as the unprocessed 24-kDa inactive precursor requiring proteolytic processing for activation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, coexpression and the dynamics of activation of different Caspases will determine the extent to which IL-18 is processed in epithelial tumor cells. In several types of tumors expressing IL-18 34,44,46 the lack of mature IL-18 has been ascribed to the absence of Caspase-1 gene expression. This does not appear to be the case in pancreatic carcinoma, since we observed high level expression of Caspase-1 mRNA and protein in the majority of tumors included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] IL-18 is crucially involved in tissue homeostasis. [27][28][29] In vivo studies have shown IL-18 expression during late stages of tumorigenesis in tumor tissues and the serum of patients with various types of cancer 30,31 together with an immunoablative role of natural killer (NK) cells. 32 Various epithelial cells express NLRs 33,34 ; however, the role of NLRs in the activation of inflammasomes within tissue-derived malignant and infected cells, as well as their direct role in controlling effector functions of intraepithelial lymphocytes (IEL), remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that by acting as an autocrine or paracrine factor, IL-18 could be produced and secreted by prostate cancer cells in response to interferon (Lebel-Binay et al, 2003). Tse et al (2011) used murine animal models of prostate cancer to investigate this mechanism and found that local expression of IL-18 in prostate cancer tissue might inhibit the development of this tumor through innate and adaptive immune pathways.…”
Section: Introductionmentioning
confidence: 99%
“…IL-18 expression in prostate cancer is also related to tumor outcome such as pathologic stage J.M. Liu et al ( Lebel-Binay et al, 2003) and the transition from androgen-responsive to hormone-refractory prostate cancer (Desai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%